Foreign direct investment : research issues - Bora, Bijit (Routledge studies in international business and the world economy ;, 2002)
Pulling together contributions from an array of international experts, this study combines theoretical with empirical work on issues such as compatable general equilibrium modelling, trade, intellectual property, environment and labour.